Surface treatment method for rigid air-permeable corneal contact lens material
By thermal polymerization reaction on the surface of the hard breathable corneal contact lens material to form a hydrophilic coating, the problem of the inability to form a stable and long-term hydrophilic coating in the prior art is solved, and the hydrophilicity and wear comfort of the lens are significantly improved.
Patent Information
- Application Number
- CN202411871968.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-14
AI Technical Summary
The existing surface treatment methods for hard breathable corneal contact lens materials cannot form a stable and long-lasting hydrophilic coating, resulting in the inability of effective improvement of the wetness of the lens.
The hydrophilic monomer solution is prepared by dissolving hydrophilic monomers on the surface of the hard breathable corneal contact lens material, and thermal polymerization is carried out at high temperature to form a stable hydrophilic coating.
This method can significantly improve the hydrophilicity of the hard breathable corneal contact lens material, reduce the water contact angle from the original 90° to about 30°, and remain basically unchanged within three months, increasing the eye comfort when wearing the lens.
Smart Images

Figure CN119613793A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of contact lens coatings, and in particular to a surface treatment method for a hard gas-permeable corneal contact lens material. Background Art
[0002] Contact lenses in use today fall into three general categories: rigid lenses made from materials prepared by polymerization of acrylates, such as polymethyl methacrylate (PMMA); rigid gas permeable (RGP) lenses made from silicone (meth)acrylates and fluorosilicone methacrylates; and soft types such as gel and hydrogel. The addition of fluorine and silicon to rigid gas permeable lenses significantly increases the oxygen permeability (Dk value) of the product, increasing the wearability of the contact lens, but makes the lens material very hydrophobic (usually with a water contact angle greater than 90°). Silicon- and fluorine-based materials are inherently hydrophobic, so any exposed silicone in the lens is likely to be non-wetting. In addition, some patients have excessive lipids in their tear film, which may deposit on the material, resulting in a foggy, hydrophobic surface. Reducing the amount of silicon and fluorine in the material can reduce the occurrence of such problems, but at the same time it will reduce the amount of oxygen permeable, resulting in a series of problems such as neovascularization, endothelial dysfunction, or corneal edema caused by insufficient oxygen supply to the eye.
[0003] At present, the surface modification methods of rigid gas permeable lenses are mainly divided into two types: plasma treatment and forming a hydrophilic coating on the surface of the material by various means. The representative plasma treatment method is Bausch and Lomb's mature marketed products (patent number: CN1117799C) and patent CN101726864B. After plasma treatment, the surface of the lens will be ionized, thereby increasing its ability to attract liquid and increasing the wetting angle, making the lens surface more hydrophilic. Therefore, plasma treatment is similar to strong cleaning of the lens, removing impurities in the manufacturing process, and improving the wettability of the lens material and the interaction with the tear film. At the same time, it can reduce fogging and provide patients with a better visual experience. There are many ways to apply a hydrophilic coating. The principle is to polymerize the hydrophilic monomer at the interface of the material to form a hydrophilic coating to increase the hydrophilic coating. Most coating methods are grafted hydrophilic monomer polymerization after plasma treatment (CN1181121C, CN1117799C, CN105111479A as examples), and there are also UV irradiation polymerization and simple immersion methods.
[0004] Plasma treatment is one of the most misunderstood concepts in rigid gas permeable lens manufacturing. It is not a true coating, but a treatment or process in which newly manufactured lenses are bombarded with high-energy radio waves in an oxygen-rich ionized gas chamber. Oxygen free radicals strike the lens surface, removing hydrocarbons (such as oils) that may have been absorbed during the manufacturing process. Nothing is permanently added to the lens; instead, the process simply changes the lens surface but does not change the basic properties of the lens material. Simple plasma surface treatment can only impart certain surface properties to the material for a short period of time. The functional groups introduced on the surface of the material will gradually move and flip inwards over time, so good properties cannot be maintained for a long time.
[0005] In addition, UV irradiation and plasma pretreatment will inevitably increase energy consumption, and the process is difficult to control during mass production. Patent CN105111479A discloses a method of plasma pretreatment and then soaking in biological hydrophilic molecular monomers. Simple soaking cannot form a stable polymer molecular layer, and there is no specific description of the timeliness of the improvement of hydrophilic properties. Therefore, it is necessary to propose a new method to form a stable and long-lasting hydrophilic coating on a hard gas permeable lens material to improve the hydrophilicity of the material. Summary of the invention
[0006] In order to solve the problem that the existing surface treatment method of hard gas permeable corneal contact lens material cannot form a stable and long-lasting coating and the wettability of the lens cannot be effectively improved, the present invention aims to propose a method for forming a long-lasting and stable hydrophilic coating on the surface of a hard gas permeable corneal contact lens material by using a hydrophilic monomer through a thermal polymerization reaction. The method can form a hydrophilic coating on the surface of the hard gas permeable corneal contact lens material, and the water contact angle of the hard gas permeable corneal contact lens material can be reduced from 90° to about 30° and the water contact angle remains basically unchanged within three months, thereby increasing the comfort of the eyes when wearing the lens, and the treatment method is energy-saving, controllable, and easy to mass-produce.
[0007] To achieve the above-mentioned purpose, in the first aspect, the present invention provides a method for treating the surface of a hard gas permeable corneal contact lens material, comprising the following steps: S1: dissolving a hydrophilic monomer in a solvent to obtain a hydrophilic monomer solution; S2: immersing the hard gas permeable corneal contact lens material in the hydrophilic monomer solution for thermal polymerization. The beneficial effect is that immersing the hard gas permeable corneal contact lens material in the hydrophilic monomer solution for thermal polymerization can add a layer of hydrophilic monomer on the surface of the hard gas permeable corneal contact lens material, thereby improving the hydrophilicity of the hard gas permeable corneal contact lens material and reducing the water contact angle of the hard gas permeable corneal contact lens material from 90° to about 30°.
[0008] In some embodiments, in S1, the solvent is an isopropanol aqueous solution, and the volume ratio of isopropanol to water is (8-9): (2-1). The beneficial effect is that when the lens material is immersed in the hydrophilic monomer solution, the monomer molecules can enter the material interface well, and the lens material will not swell completely.
[0009] In some embodiments, before S2, the steps include: deoxygenating the hydrophilic monomer solution; and adding a redox agent to the deoxygenated hydrophilic monomer solution. The beneficial effect is that the pre-deoxygenation operation of the hydrophilic monomer solution can eliminate the influence of oxygen on the polymerization reaction.
[0010] In some embodiments, before S2, the method further includes: adding a cleaning agent into a cleaning device, and then adding the hard gas permeable corneal contact lens material into the cleaning device for cleaning.
[0011] In some embodiments, the redox agent is ammonium ferrous sulfate, and the mass percentage of the ammonium ferrous sulfate is 0.2 to 1 wt%.
[0012] In some embodiments, S2 includes: immersing the hard gas permeable corneal contact lens material in the hydrophilic monomer solution, heating it to 65-75°C, and reacting it for 20-24 hours. The beneficial effect is that the redox agent can act as an initiator after meeting the temperature conditions, decomposing to produce ionic active substances, attacking the monomer molecules, opening their double bonds and initiating a chain polymerization reaction.
[0013] In some embodiments, the hydrophilic monomer is 2-methacryloyloxyphosphocholine. Its beneficial effect is that 2-methacryloyloxyphosphocholine is a biomimetic macromolecule with high hydrophilicity and good biocompatibility. Its structure is similar to that of biological membranes. It can be used for surface modification of biomaterials to significantly improve the hydrophilicity and biocompatibility of the materials and reduce the adsorption of lipids on the surface of the materials.
[0014] In some embodiments, the mass fraction of the 2-methacryloyloxyphosphorylcholine is 10-20 wt %. The beneficial effect is that the coating with a mass fraction of 10-20 wt % of 2-methacryloyloxyphosphorylcholine has the best effect.
[0015] In some embodiments, the deoxygenation time is 25 to 35 minutes.
[0016] In some embodiments, the cleaning device is an ultrasonic cleaner; and the cleaning time is 20 to 40 minutes.
[0017] The beneficial effect of the present invention is that: through the treatment method of the present invention, a stable hydrophilic coating can be formed on the surface of the hard gas permeable corneal contact lens material, so that the hydrophilic property of the lens after surface treatment is significantly improved, and its water contact angle can be reduced from 90° to about 30°, and the water contact angle remains basically unchanged within three months. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a flow chart of a method for treating the surface of a hard gas permeable contact lens material according to an embodiment of the present invention; Figure 2 The water contact angle of the hard gas permeable corneal contact lens material before being treated in Example 1 of the present invention; Figure 3 is the water contact angle of the hard gas permeable corneal contact lens material after treatment in Example 1 (0 day); Figure 4 is the water contact angle of the hard gas permeable corneal contact lens material after treatment (3 months) in Example 1; Figure 5 The water contact angle of the hard gas permeable corneal contact lens material before being treated in Example 2 of the present invention; Figure 6 is the water contact angle after the hard gas permeable corneal contact lens material is treated in Example 2 (0 day); Figure 7 This is the water contact angle of the hard gas permeable corneal contact lens material of Example 2 after treatment (3 months). DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the accompanying drawings of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the usual meanings understood by people with general skills in the field to which the present invention belongs. "Including" and similar words used in this article mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Unless otherwise specified, the "connection" described in this article can be a direct connection or an indirect connection, that is, connected through an intermediate.
[0019] In view of the problems existing in the prior art, an embodiment of the present invention provides a surface treatment method for a rigid gas permeable corneal contact lens material, comprising the following steps: S1: dissolving a hydrophilic monomer in a solvent to obtain a hydrophilic monomer solution; S2: immersing the rigid gas permeable corneal contact lens material in the hydrophilic monomer solution to carry out a thermal polymerization reaction.
[0020] In some embodiments, in S1: the solvent is an isopropanol aqueous solution, and the volume ratio of isopropanol to water is (8-9): (2-1).
[0021] In some embodiments, before S2, the steps include: deoxygenating the hydrophilic monomer solution; and adding a redox agent to the deoxygenated hydrophilic monomer solution.
[0022] In some embodiments, before S2, the method further includes: adding a cleaning agent into a cleaning device, and then adding the hard gas permeable corneal contact lens material into the cleaning device for cleaning.
[0023] In this embodiment, the cleaning agent may be deionized water. The surface of the hard gas permeable corneal contact lens material may be polished to remove tiny scratches and impurities on the surface of the contact lens material, and at the same time make the edge of the contact lens material smoother, thereby improving the optical performance and the safety and comfort when wearing. Further cleaning of the polished contact lens material may further remove impurities on the lens surface, ensuring that there are no foreign objects on the lens surface that hinder the grafted hydrophilic coating. After cleaning, the hard gas permeable corneal contact lens material may be dried.
[0024] In some embodiments, the redox agent is ammonium ferrous sulfate, and the mass percentage of the ammonium ferrous sulfate is 0.2 to 1 wt%.
[0025] In some embodiments, S2 includes: immersing the hard gas permeable corneal contact lens material in the hydrophilic monomer solution, sealing the hydrophilic monomer solution, heating it to 65-75° C., and reacting it for 20-24 hours.
[0026] In this embodiment, after the reaction is completed, the surface of the hard gas permeable corneal contact lens material has been grafted with a hydrophilic coating. The hard gas permeable corneal contact lens material is taken out and cleaned with an ultrasonic cleaner to remove the unpolymerized hydrophilic monomers on the surface of the hard gas permeable corneal contact lens material. After cleaning, the material is dried and stored at room temperature.
[0027] In some embodiments, the hydrophilic monomer is: 2-methacryloyloxyphosphocholine.
[0028] In this embodiment, the hydrophilic monomer may also be: 2-methacryloyloxyethyl phosphorylcholine, polyethylene glycol diacrylate or polyethylene glycol.
[0029] In some embodiments, the mass fraction of the 2-methacryloyloxyphosphocholine is 10-20 wt%.
[0030] In some embodiments, the deoxygenation time is 25 to 35 minutes.
[0031] In this embodiment, nitrogen gas may be introduced into the hydrophilic monomer solution for deoxygenation.
[0032] In some embodiments, the cleaning device is an ultrasonic cleaner; and the cleaning time is 20 to 40 minutes.
[0033] The present invention is further described below by specific examples. Unless otherwise specified, the reagents, materials and instruments used below are all conventional reagents, conventional materials and conventional instruments, which can be obtained commercially, and the reagents and materials involved can also be synthesized by conventional synthesis methods.
[0034] Example 1 1) Polish the hard gas permeable corneal contact lens material (Boston XO2, Shanghai Micro-Invasive Vision), add deionized water to a CNC ultrasonic cleaner, put the hard gas permeable corneal contact lens material in and clean it for 20 minutes. After ultrasonic cleaning, dry and store it at room temperature.
[0035] 2) 2-methacryloyloxyphosphocholine (MPC) was dissolved in an isopropanol-water solvent with a volume ratio of 8:2 to prepare a 20 wt% MPC solution. Nitrogen was introduced into the 20 wt% MPC solution for deoxygenation for 25 min, the treated lens material was placed in it, 1 wt% ammonium ferrous sulfate was added, and the reaction was carried out in a sealed manner at 70°C for 20 h.
[0036] 3) Add deionized water to a CNC ultrasonic cleaner, put in the hard gas permeable corneal contact lens material and clean for 15 minutes. After ultrasonic cleaning, dry and store at room temperature.
[0037] Figure 2 The water contact angle of the lens material before treatment in Example 1, Figure 3 is the water contact angle of the lens material after treatment in Example 1 (0 days), Figure 4 This is the water contact angle of the lens material after treatment in Example 1 (3 months).
[0038] Example 2 1) Polish the hard gas permeable corneal contact lens (Boston XO2, Shanghai Micro-Invasive Vision), add deionized water to the CNC ultrasonic cleaner, put in the hard gas permeable corneal contact lens material and clean for 20 minutes. After ultrasonic cleaning, dry and store at room temperature.
[0039] 2) 2-methacryloyloxyphosphocholine (MPC) was dissolved in an isopropanol-water solvent with a volume ratio of 9:1 to prepare a 10 wt% MPC solution. Nitrogen was passed into the 10 wt% MPC solution for deoxygenation for 35 min, the treated lens material was placed in it, 0.25 wt% ammonium ferrous sulfate was added, and the reaction was carried out in a sealed state at 70°C for 24 h.
[0040] 3) Add deionized water to a CNC ultrasonic cleaner, put in the hard gas permeable corneal contact lens material and clean for 30 minutes. After ultrasonic cleaning, dry and store at room temperature.
[0041] Figure 5 The water contact angle of the lens material before treatment in Example 2, Figure 5 is the water contact angle of the lens material after treatment in Example 2 (0 days), Figure 7 This is the water contact angle of the lens material after treatment in Example 2 (3 months).
[0042] The above is only a specific implementation of the embodiment of the present application, but the protection scope of the embodiment of the present application is not limited thereto, and any changes or replacements within the technical scope disclosed in the embodiment of the present application should be included in the protection scope of the embodiment of the present application. Therefore, the protection scope of the embodiment of the present application should be based on the protection scope of the claims.
Claims
1. A method for treating the surface of a hard gas permeable contact lens material, characterized in that: The following steps are involved: S1: dissolving a hydrophilic monomer in a solvent to obtain a hydrophilic monomer solution; S2: Immersing the rigid gas permeable corneal contact lens material into the hydrophilic monomer solution to carry out a thermal polymerization reaction.
2. The method for surface treatment of a hard gas permeable contact lens material according to claim 1, characterized in that: In S1: The solvent is an isopropanol aqueous solution, and the volume ratio of isopropanol to water in the isopropanol aqueous solution is (8-9): (2-1).
3. The method for surface treatment of a hard gas permeable contact lens material according to claim 1, characterized in that: Before said S2 includes: Deoxygenating the hydrophilic monomer solution; A redox agent is added to the deoxygenated hydrophilic monomer solution.
4. The method for surface treatment of a hard gas permeable contact lens material according to claim 1, characterized in that: Before the S2, it also includes: A cleaning agent is added into a cleaning device, and then the hard gas-permeable corneal contact lens material is added into the cleaning device for cleaning.
5. The method for surface treatment of a hard gas permeable contact lens material according to claim 3, characterized in that: The redox agent is ammonium ferrous sulfate, and the mass percentage of the ammonium ferrous sulfate is 0.2-1 wt%.
6. The method for surface treatment of a hard gas permeable contact lens material according to claim 1, characterized in that: The S2 includes: The rigid gas permeable corneal contact lens material is immersed in the hydrophilic monomer solution, sealed and heated to 65-75° C., and reacted for 20-24 hours.
7. The method for surface treatment of a hard gas permeable contact lens material according to claim 1, characterized in that: The hydrophilic monomer is: 2-methacryloyloxyphosphocholine.
8. The method for surface treatment of a hard gas permeable contact lens material according to claim 7, characterized in that: The mass fraction of the 2-methacryloyloxyphosphocholine is 10-20 wt%.
9. The method for surface treatment of a hard gas permeable contact lens material according to claim 3, characterized in that: The deoxygenation time is 25 to 35 minutes.
10. The method for surface treatment of a hard gas permeable contact lens material according to claim 4, characterized in that: The cleaning equipment is an ultrasonic cleaner; the cleaning time is 20 to 40 minutes.
Citation Information
Patent Citations
Plasma hydrophilic modification method for the surface of fluorosilicone rigid corneal contact lenses
CN101726864B
Method for modifying fluorinated siloxane acrylate material of rigid gas-permeable corneal contact lens
CN105111479A
Plasma surface treatment of silicone hydrogel contact lenses with flexible carbon coating
CN1117799C
Surface treatment for silicone hydrogel contact lenses comprising hydrophilic polymer chains attached to intermediate carbon coating
CN1181121C